2006
DOI: 10.1111/j.1365-2605.2005.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated European investigations of semen quality: results from studies of Scandinavian young men is a matter of concern

Abstract: For many years it has been acknowledged that Danish and Norwegian men have one of the highest risks in the world for testicular cancer in sharp contrast to neighbouring Baltic men from Finland, Estonia and Lithuania. As an association between poor semen quality and testicular cancer has been established, it was suggested that men from high-risk testicular cancer areas would be more likely to have poor semen quality. However, previous studies were not able to elucidate this question due to their retrospective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 60 publications
(112 reference statements)
1
107
0
7
Order By: Relevance
“…The only two completely random samples came from Denmark, but the sperm quality of men in this country is reputed to be among the lowest in Europe. 25 It appeared that the median concentration and motility of sperm from our study population were in line with those of sperm from non-selected, young Danish men, either undergoing an examination for military service 26 or being Danish trade union members without children or known fertility problems. 27 Nowadays, patients with intermediate or poor quality sperm are still eligible to enter sperm cryopreservation programs with a view to subsequent in vitro fertilization or intracytoplasmatic sperm injection.…”
Section: Discussionmentioning
confidence: 63%
“…The only two completely random samples came from Denmark, but the sperm quality of men in this country is reputed to be among the lowest in Europe. 25 It appeared that the median concentration and motility of sperm from our study population were in line with those of sperm from non-selected, young Danish men, either undergoing an examination for military service 26 or being Danish trade union members without children or known fertility problems. 27 Nowadays, patients with intermediate or poor quality sperm are still eligible to enter sperm cryopreservation programs with a view to subsequent in vitro fertilization or intracytoplasmatic sperm injection.…”
Section: Discussionmentioning
confidence: 63%
“…It has been suggested that it may be indicative of a common underlying (fetal) cause (18), and our present animal experimental studies provide direct supporting evidence for this suggestion. This suggested connection has widespread implications, because one in six young men in northern European countries has a low sperm count (<20 million/mL) (68), and testosterone levels in men of all ages are declining (4-6). Moreover, it has implications for morbidities associated with aging and the aging-related decline in testosterone levels (3,(7)(8)(9)69), because ∼10% of aging men exhibit compensated Leydig cell failure (7).…”
Section: -Hsd3mentioning
confidence: 99%
“…In several European countries 20% or more of young men may have abnormally low sperm counts relative to World Health Organization criteria [1]. As each Sertoli cell (SC) can support a finite number of germ cells, the number of SCs is a key factor in determining testis size and the number of spermatozoa in adulthood [2].…”
Section: Introductionmentioning
confidence: 99%